Isolation of Cryptococcus gattii from a Castanopsis argyrophylla tree hollow (Mai-Kaw), Chiang Mai, Thailand - Kantarawee Khayhan (2018)
© 2017, Springer Science+Business Media Dordrecht. The pathogenic yeast Cryptococcus gattii was isolated from a tree hollow of a Castanopsis argyrophylla King ex Hook.f. (Fagaceae) in Chiang Mai, Thailand. Molecular characterization with amplified fragment length polymorphism analysis and multi-locus sequence typing showed that this isolate belonged to genotype AFLP4/VGI representing C. gattii sensu stricto. Subsequent comparison of the environmental isolate with those from clinical samples from Thailand showed that they grouped closely together in a single cluster.